Baboon cytochrome P450 c17 (17[alpha]-hydroxylase/17, 20 lyase) : cDNA cloning from adrenal mRNA and characterisation of the expressed enzyme - Swart, Amanda C.(Amanda Cecilia) (Stellenbosch : Stellenbosch University, 2012)
In title the alpha is a Greek letter.